Morphological changes of rat peripheral nerve under chronic micromercurialism and its pharmacological correction in different terms after injury. - Shamalо, S. N. (Морфологія / Morphologia / Morfologìâ, 2015)
Background. Search for new pharmacological agents that activate processes of traumatized nerve regeneration at the condition of mercurial intoxication remains urgent. Objective. The aim of this study was a comparative morphometric analysis of rat peripheral nerve under micromercurialism using antioxidant drug without pharmacotherapy. Methods. Experimental model of sciatic nerve trauma under conditions of chronic micromercurialism was investigated in experiments on two groups of white rats. Micromercurialism was modeled by intraperitoneal injection of mercuric chloride during 10 weeks before sciatic nerve trauma. The rats of the first group received no pharmacological drugs in postoperative period. The second group of animals received 100 μg/kg solution of Thiotriazolinum intraperitoneally daily during 2 weeks after operation. The morphological organization and morphometric data of regenerative neuroma and adjoining parts (proximal and distal) of sciatic nerve were studied in 6 and 12 weeks after damage using morphometric and statistic methods. Results. Basing on the results of the second group of animals the average angle of axon deviation from the axis of the nerve in the neuroma sufficiently decreases and distribution density of neuron fibers in distal part increases comparing with the first group. Conclusion. Taken together these data evidence that Thiotriazolinum improves the process of traumatized nerve regeneration